Counting on My Vote Not Counting: Expressive Voting in Committees (2020)
A committee chooses whether to approve a proposal that some members may consider ethical. Members who vote for the proposal receive expressive utility, and all pay a cost if the proposal is accepted. Committee members have di erent depths of reasoning. The model predicts that features that reduce the probability of being pivotal - namely, larger committee size, or a more restrictive voting rule - raise the share of votes for the proposal. A laboratory experiment with a charitable donation framing supports these results. Our structural estimation recovers the distributions of altruistic and expressive preferences, and of depth of reasoning, across individuals.